New Insights Related to Rechargeable Lithium Batteries: Li Metal Anodes, Ni Rich LiNixCoyMnzO2 Cathodes and Beyond Them. Issue 3 (2nd January 2019) - Markevich, Elena; Salitra, Gregory; Hartmann, Pascal; Kulisch, Joern; Aurbach, Doron; Park, Kang-Joon; Yoon, Chong S.; Sun, Yang-Kook
Abstract : The electro-mobility revolution challenges the batteries community to develop rechargeable batteries with the highest energy density, including the use of Li metal anodes. Relevant cathode materials include sulfur and molecules with the general formula LiNix Coy Mnz O2, denoted as Ni rich NCM (x+y+z = 1; x > 0.5). We discuss herein new insights obtained from our recent work with cells comprising Li metal anodes, LiNi0.6 Co0.2 Mn0.2 O2 and LiNiO2 cathodes with practical charge density higher than 3 mAh/cm 2 . Highly stable behavior of Li metal anodes was realized in solutions containing mono-fluorinated ethylene carbonate (FEC) as a co-solvent. We found that the same solutions stabilize Ni rich NCM cathodes as well. We discuss herein the limiting factor of Li-LiNiO2 cells in terms of cycle life and have gained new understandings related to failure and stabilization mechanisms of Ni rich NCM cathodes. Providing that the electro-mobility revolution succeeds, we may encounter a shortage in the availability of nickel. We suggest herein strategies for handling this problem by the use of Mn based cathodes.